Engineering of Piroxicam Agglomerates by Additives Using Wet Agglomeration Technique - Maryam Maghsoodi 1 * (Tabriz University of Medical Sciences, 2016)
Background: Wet agglomeration is a method wherein the crystals of dispersion are held together in aggregates by small amount of a liquid acting as an intercrystal binder. In present study, in order to study the possible modification of agglomerate structure, low concentrations of additives (0.1-1%) were added to binder liquid. Methods: Piroxicam agglomerates were produced by wet agglomeration method by three solvent systems including a good solvent (dimethylformamide or acetone), antisolvent (water) and a binder liquid (ethylacetate or isopropylacetate). Span 80, talc, ethylcellulose and Eudragit RS in different concentrations were used as additives. The agglomerates were evaluated for production yield of agglomerates, size, friability and drug release properties. Results: The results showed that formation of agglomerates was possible in presence of span and talc. However, no agglomerates could be obtained with polymers tested (ethylcellulose and Eudragit RS). Talc increased agglomerate size, whereas the obtained agglomerates were more susceptible to breakup. However, using span as opposed to talc resulted in agglomerates with higher strength but smaller particle size. The dissolution tests showed that both additives adversely affected the dissolution rate of piroxicam from the agglomerates. Conclusion: Result of this study suggested that additives even in small amounts played a major role in agglomerate properties.